Relation of shear stress and K L a on bikaverin production by Fusarium oxysporum CCT7620 in a bioreactor - dos Santos, Marcela Colombo; Cerri, Marcel O. [UNESP]; Bicas, Juliano Lemos (Springer Nature, 2022)
This study involved evaluating the effects of rotational impeller speed agitation (N) and specific air flow rate (Фair) on bikaverin production and on the growth of Fusarium oxysporum employing 11 bench-scale bioreactor assays. The results showed that the maximum bikaverin production (close to 300 mg L−1) was achieved after 48 h of fermentation in rice medium (20 g L−1 milled rice in water) at 28 °C with a volumetric oxygen transfer coefficient (KLa) and shear stress values of approximately 20 h−1 and 17 N m−2, respectively. We reached this combination of parameters using an N of 340 rpm and Фair of 0.935 vvm. These KLa and shear stress values can be used as references when upscaling this process. Thus, this study was important to demonstrate how the main parameters in bioreactors affect bikaverin production and it presented important indications for upscaling this bioprocess.
Keywords: Blue pigment; Optimization; Scale-up; Shear stress; Volumetric oxygen transfer coefficient (KLa)